The Relationship between Flexible and Adaptive Behaviour Ability and Students' Tolerance Attitude: A Correlational Approach - Vera Sapitri; M. Nurudin; Muhammad Arham Prasetyo; M.Yusuf Qordowi; Muhammad Hafiz Putra; Nurul Azizah (Action Research Journal Indonesia (ARJI), 2025)
The level of tolerance among students is an important issue in the midst of social diversity today. Flexibility and adaptability are often considered as supporting factors for tolerant attitudes. This study aims to analyse the correlation between skills in being flexible and adaptable and the level of tolerance of students at SMA Negeri 15 Bandar Lampung. The method used was quantitative correlation with a sample of 74 randomly selected respondents. Data were collected through a Likert scale questionnaire, then analysed with non-parametric tests considering the data were not normally distributed. The results of the analysis showed no significant correlation between flexibility and adaptability with tolerance (significance value above 0.05). This suggests that other factors, such as environmental influences, multicultural learning, and the cultivation of Pancasila values are more dominant in shaping tolerance. The implications of this study emphasise the need for educators to develop comprehensive character building programmes, not limited to flexibility training, but also including other dimensions such as empathy training and real social interaction. Future research is expected to explore other factors that could potentially influence students' tolerance levels, such as the role of character education, family environment, and cross-cultural experiences. In addition, it is recommended to use a mixed methods approach to gain a deeper understanding of the dynamics of tolerance attitude formation among students.